O1-S07.03 Prevalence and correlates of rectal chlamydia and gonorrhoea among female STD clinic clients. (10th July 2011) - Javanbakht, M; Guerry, S; Stirland, A; Gorbach, P; Kerndt, P
Abstract : Background: The prevalence and correlates of rectal sexually transmitted infections (STI) are well described among men who report receptive anal intercourse (AI). However, very little is known about the epidemiology of rectal STIs among women. Methods: We conducted a cross-sectional study of women attending twelve public STD clinics in Los Angeles County, California. Women were eligible for inclusion in this study if they reported AI in the previous 90 days, were tested for rectal chlamydia (CT) and gonorrhoea (GC), and were seen between January 2008 and December 2009. Data collected included demographics, types of sexual contact, substance use, other risk behaviours, and STI results. Results Among the 716 females included in this analysis, the median age was 28 years (range 14–60), 40% were Hispanic, 37% African American, and 15% White. The prevalence of CT and GC by anatomic site was: 11.8% (n=83) urogenital CT, 14.2% (n=100) rectal CT, 2.7% (n=19) urogenital GC, and 3.0% (n=21) rectal GC. Among positives, 27% of CT cases and 27% of GC cases had rectal only infections. Among women =25 years the prevalence of rectal infections was higher among those incarcerated in the past year (39.4% vs 22.1%; p value=0.03) and those who reported sex with an injection drug user (50.0% vs 23.3%; p value=0.05). Among women >25 years the prevalence of rectal infections was higher among those with longer term sex partners (ie, >90 days; 12.6% vs 5.9%; p value=0.03), and those who reported substance use (14.8% vs 8.3%; p value=0.04). While the number of women with a rectal-only infections (ie, no urogenital infection; n=33) was small, similar trends were observed. After controlling for age and race/ethnicity, among women ≥25 years those incarcerated in the previous year were more likely to have a rectal infection (adjusted OR [AOR]=2.55; 95% CI 1.14% to 5.71%). Among women >25 years, after controlling for race/ethnicity and age, those who reported substance use were more likely to have a rectal infection (AOR=2.28; 95% CI 1.14% to 4.55%) while those reporting new sex partners were less likely to have a rectal infection (AOR=0.38; 95% CI 0.16% to 0.88%). Conclusion: These findings highlight that the prevalence of rectal Chlamydia and gonorrhoea among women is similar to that of urogenital infections and a relatively large number of infections would be missed in the absence of rectal testing. Factors associated with rectal infections may differ by age.